On the impact of policy uncertainty on oil prices: An asymmetry analysis - Mohsen Bahmani-Oskooee; Hanafiah Harvey; Farhang Niroomand (International Journal of Financial Studies, 2018)
Previous research has assessed the impact of policy uncertainty on a few macro variables. In this paper, we consider its impact on oil prices. Oil prices are usually determined in global markets by the law of demand and supply. Our concern in this paper is to determine which country's policy uncertainty measure has an impact on oil prices. Using both the linear and the nonlinear Autoregressive Distributed Lag (ARDL) methods, we find that while policy uncertainty measures of Canada, China, Europe, Japan, Russia, South Korea, and the U.S. have short-run effects, short-run effects last into the long-run asymmetric effects only in the case of China. This may reflect the importance and recent surge in China's engagement in world trade.
Keywords: D81; D82; O13; 330; policy uncertainty; oil prices; asymmetry; nonlinear ARDL approach